Brachiaria brizantha cv. Marandu response to nitrogen fertilizers associated to natural reactive phosphate - Avelino Cabral, Carlos Eduardo; Cabral, Luciano da Silva; Bonfim-Silva, Edna Maria; Carvalho, Kassio dos Santos; Kroth, Bruna Elusa; Cabral, Carla Heloisa Avelino (Comunicata Scientiae, 2016)
This study aimed to identify a proportion of urea and ammonium sulfate associated to natural reactive phosphate that coud maximize the production of ‘marandu’ grass in a red clayay oxisol with low phosphorus content. The experiment was conducted in a greenhouse with a completely randomized design , in split plots in the time with seven repetitions. The main plots consisted of six levels of the substitution of urea by ammonium sulfate: 0, 20, 40, 60, 80 and 100%. The split plots consisted of three growth periods, being the first 30 days after plants emergence and the others spaced 20 days after the previous evaluation. The evaluated variables were: number of tillers, SPAD value, shoot, leaf blade and stem dry mass. The ammonium sulfate can provide higher soil acidity when compared to urea, which contributes to the reactive phosphate solubilization. Ammonium sulfate increment changes the SPAD value of ‘marandu’ grass fertilized with natural reactive phosphate.